Tecnica e libertà fra Praga e Santiago - Andrea Cerroni (Quaderni di Sociologia)
With the 1973 Chilean coup there was a total change in the economic order, from Allende’s socialist experiment (original in its “balancing” of center and periphery) to the full adoption of neoliberalism, which was accompanied by a simultaneous transition in the IT field. In fact, Allende’s experience was so closely linked to the development of the first, futuristic cybernetical project for the governance of the technological-information infrastructure (Cybersyn), which was promptly scrapped after the coup. A similar outcome to this sudden defeat of cybernetics, had actually occurred during the Prague Spring. Later, as neoliberalism spread, cybernetics faded in favor of a rival approach to information science, so-called Artificial Intelligence. This article will attempt to answer the following questions. (1) Were there fundamental cultural divergences between cybernetics and artificial intelligence such that they really resonated with two alternative policy perspectives? (2) Can one, moreover, delineate a kind of symbolic universe that would extend from the (then prospective) artificial intelligence to the paradigms later established in many disciplines?